Molecular cloning of EZH2 oncogene in chronic myeloid leukemia and therapeutic prospects - Juliana Costa Gaspar; Lucas Santos de Santana; Camila Menezes Freire de Souza; Marcos Montani Caseiro; Rosane Rezende de Souza Giuliani; Cleide Barbieri de Souza (O Mundo da Saúde)
Chronic myeloid leukemia (CML) is a myeloproliferative neoplasia, caused in 95 % of the cases by a cytogenetic abnormality characterized by the reciprocal translocation between chromosomes 9 and 22 t(9; 22) (q34; q11), resulting in Philadelphia chromosome (Ph).Considering that CML cure is only possible with a successful bone marrow transplantation and that there are resistance cases to the tyrosine kinase inhibitor Imatinib Mesylate, prescribed in first line drug treatment; it is important to know in detail the genes and proteins that are possibly altered in CML, favoring effective therapeutic strategies, optimized diagnosis and minimal residual disease detection. Among the new therapeutic approaches to CML is gene therapy, which, depending on the target gene, can be efficient to other neoplasms treatment. In this context, the aims of this work were: to proceed the molecular cloning of a DNA fragment from EZH2 gene, potential target for gene therapy, that promotes epigenetic alteration in CML and in many neoplasms; as well as to contribute to studies related to interspecies gene transfer that have high contribution to health. For this reason, the EZH2 gene was isolated from peripheral blood genomic DNA from CML patients and cloned in prokaryotic systems. Therefore, in this study, we proceed, defined and proved the interspe- cies gene transfer procedures and discussed the future of biotechnology in researches and treatments, especially in CML.